2014
DOI: 10.1002/ajmg.c.31407
|View full text |Cite
|
Sign up to set email alerts
|

Genotype‐phenotype correlation of Coffin‐Siris syndrome caused by mutations in SMARCB1, SMARCA4, SMARCE1, and ARID1A

Abstract: Coffin-Siris syndrome (CSS) is a rare congenital malformation syndrome, recently found to be caused by mutations in several genes encoding components of the BAF complex. To date, 109 patients have been reported with their mutations: SMARCB1 (12%), SMARCA4 (11%), SMARCE1 (2%), ARID1A (7%), ARID1B (65%), and PHF6 (2%). We review genotype-phenotype correlation of all previously reported patients with mutations in SMARCB1, SMARCA4, SMARCE1, and ARID1A through reassessment of their clinical and molecular findings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
141
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(151 citation statements)
references
References 13 publications
4
141
1
5
Order By: Relevance
“…Haploinsufficiency of ARID1B has been identified as a frequent cause of intellectual disability, agenesis of the corpus callosum [12,13], and autism [14,15]; and mutations in ARID1A and ARID1B cause Coffin-Siris syndrome [16,17]. Studies also have identified other core catalytic units of the SWI/SNF complexes as causes of neurological diseases, including SMARCA2 in Nicolaides-Baraitser syndrome (NBS) [18] and SMARCB1, SMARCA4, and SMARCE1 in CoffinSiris syndrome [19].…”
Section: Introductionmentioning
confidence: 96%
“…Haploinsufficiency of ARID1B has been identified as a frequent cause of intellectual disability, agenesis of the corpus callosum [12,13], and autism [14,15]; and mutations in ARID1A and ARID1B cause Coffin-Siris syndrome [16,17]. Studies also have identified other core catalytic units of the SWI/SNF complexes as causes of neurological diseases, including SMARCA2 in Nicolaides-Baraitser syndrome (NBS) [18] and SMARCB1, SMARCA4, and SMARCE1 in CoffinSiris syndrome [19].…”
Section: Introductionmentioning
confidence: 96%
“…Скрининг на мутации в генах SWI/SNF-комплекса показал, что 80% пациентов с синдромом Коффина -Сириса несут герминаль-ную мутацию в одном из них [6]. К настоящему времени описаны 109 пациентов с мутациями в 6 генах комплекса SWI/SNF, частоты которых распределены следующим образом: SMARCB1 -12%, SMARCA4 -11%, SMARCE1 -2%, ARID1A -8%, ARID1B -65% и PHF6 -2% [33]. Несмотря на то что чаще всего мутации обнаруживали в гене ARID1B, классический тип синдрома Коффина -Сириса связан в первую очередь с мутациями SMARCB1.…”
Section: герминальные мутации Smarcb1 при синдроме коффина -сирисаunclassified
“…Кроме того, если в других перечисленных генах не наблюдали «горячие точки» мутагенеза, то все мутации SMARCB1 при синдроме Коффина -Сириса локализованы в 8-9-м экзонах, кодирую-щих С-конец белка, рядом с консервативной по-следовательностью SNF5-домена. Самой частой мутацией независимо от популяционной принад-лежности является p.K364del [32,33]. Именно поэ-тому SMARCB1 при синдроме Коффина -Сириса представляет собой удобную мишень для пря-мой ДНК-диагностики.…”
Section: герминальные мутации Smarcb1 при синдроме коффина -сирисаunclassified
See 1 more Smart Citation
“…Coffin-Siris syndrome (CSS) (MIM 135900) is congenital associated with intellectual disability or developmental delay, hypoplastic fifth fingernails, and patterning defects in the head (broad nasal bridge, low set ears, cleft palate, choanal atresia, hearing loss) and heart (ventricular septal defects or VSDs, malposition of great arteries, and patent ductus arteriosus) (Kosho et al, 2014; Kosho et al, 2013; Schrier et al, 2012). The most severe cases of CSS result in intrauterine or early childhood death with associated cardiac defects (Coulibaly et al, 2010; Kosho et al, 2014; Kosho et al, 2013; Nemani et al, 2014; Santen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%